Job Management System for Cell Monitoring Services - Harry Ariyanto Putra (Institute of Research and Community Outreach - Petra Christian University, 2020)
The assignment was initiated and given by CytoSmart Technologies B.V., which specializes in providing a solution to track the behavior of the cells. One of the devices, called Omni, makes it possible to take multiple images of cells and then process them, e.g. cell colony detection, in the cloud by using algorithm selected by the customers. For each experiment initiated by the customers, Omni takes multiples images from the cells and uploads them to the cloud. In the cloud, the images will be combined and processed according to the algorithm selected by the customers. These processes are running in the cloud and are repeated based on the interval that are defined by the customer. Currently there are no solution implemented to track and know what is happening there. Until now, the operational team must check the databases directly to find out if there is any problem. Besides that, to re-do the experiment, failed or not, the operational team must re-do the experiment from start. The system will provide a way to track and manage the process that is happening in the cloud and also provide a feature to re-do the experiment. The intern managed to implement the tracking of the processes and at the same time make the code maintainable and extendable. Reprocessing functionality was also implemented successfully. The solution is built using ASP .NET Core and other in-trend technologies, such as Vue.js, Microsoft Azure, etc.